The behaviour of real estate actors and cyclicality in the Real Estate Market - Cronje, Pierre (Department of Construction Economics and Management, 2020)
The proposed research aims to gain a better understanding of the information inefficiencies in the real estate investment milieu through the exploration of the behaviour of real estate actors. The supposition is that a better understanding of the real estate actor behaviour in the context of market cyclicality should add to the body of knowledge on the pro-active mitigation of real estate investment losses. The exogenous factors causing market cyclicality such as the sub-prime mortgage crises of 2007/2008 is used analogously to an independent variable with the focus on the behaviour and interrelation of real estate actors or endogenous causes of market cyclicality. A phenomenological approach in the context of constructivist ontology is followed in a connected mixed method research strategy, i.e. a quantitative to qualitative sequential explanatory design to explore the behaviour of the real estate user, - developer and - investor. The quantitative data analysis takes the form of descriptive statistics of office vacancy rates, - areas and - capitalisation rates of seven nodes in Cape Town. Although inferential statistical methods, such as the nonparametric Kruskal-Wallis Test, linear tend analysis and measures of linearity are used it is still used in the form of descriptive statistics to understand phenomena and extrapolate results to other situations. Qualitative data are collected through semi-structured interviews and analysis is done with Giorgi’s descriptive phenomenology approach to synthesise a general psychological structure based on the constituent of the participant’s experience. The study found that regular periods of over- and underbuilding in the real estate market may be influenced by the real estate actor because of the bounded nature of information and bounded capability of the actor. Real estate actors display behaviour actively avoiding the negative impact of market cyclicality through the use of agency. An agency based model is developed through this study showing that the real estate actor use specialisation to confine the unknown nature of information and to liberate the bounded ability of the real estate actor through working the network, engaging the network and signalling.